ALUNOS COM MOTIVAÇÃO INSTRUMENTAL EM UM CURSO DE INGLÊS GERAL: UM CONFLITO DE OBJETIVOS? - Acosta, Maria Aparecida Gazotti Vallim (Intercâmbio, 2010)
This paper reports a study on how ESP1 students in a GE2 course establish their learning goals according to the perceptions they have of their needs in the target situation. Data were collected by means of semi-structured interviews, class observation and journals. The analysis of the data was founded on the concepts of objective and subjective needs discussed by Brindley (1989).